Inflammatory markers link triglyceride-glucose index and obesity indicators with adverse cardiovascular events in patients with hypertension: insights from three cohorts - Yanqiu Huang; Yi Zhou; Yadan Xu; Xiaoyu Wang; Ziyi Zhou; Kang Wu; Qiqi Meng; Liao Wang; Yang Yang; Hong Gao; Juan Ji; Xu Jiang; et al. (Cardiovascular Diabetology)
Abstract Background Among hypertensive cohorts across different nations, the relationship between the triglyceride-glucose index (TyG) and its conjunction with obesity metrics in relation to cardiovascular disease (CVD) incidence and mortality remains to be elucidated. Methods This study enrolled 9,283, 164,357, and 5,334 hypertensives from the National Health and Nutrition Examination Survey (NHANES), UK Biobank (UKBB), and Shanghai Pudong cohort. The related outcomes for CVD were defined by multivariate Cox proportional hazards models, Generalized Additive Models and Mendelian randomization analysis. Mediation analysis explored the mediating role of inflammatory markers in the above relationships. Results Five measures of insulin resistance were linked to CVD and related death in a U-shaped pattern, with the highest group having different risk increases. Higher glucose triglyceride-waist height ratio (TyG-WHTR) was linked to higher all-cause mortality (UKBB: HR 1.21, 95%CI 1.16–1.26, NHANES: HR 1.17, 95%CI 1.00–1.36), CVD mortality (UKBB: HR 1.36, 95%CI 1.23–1.49, NHANES: HR 1.32, 95%CI 1.00–1.72) risks. In the China Pudong cohort, higher triglyceride/high-density lipoprotein-cholesterol (TG/HDL_C) ratio was associated with higher risks of CVD and stroke (HR 1.31, 95%CI 1.00–1.73 and 1.67, 1.06–2.63). Inflammation markers like systemic inflammatory response index (SIRI) and C-reactive protein (CRP) partially explained these links, with CRP having a stronger effect. Genetically predicted TyG was also linked to stroke (OR 1.26, 95%CI 1.10–1.45) risk. Conclusions An elevated TyG index and its related indices are significantly correlated with an increased risk of CVD and related mortality across three national cohorts. These indices are anticipated to serve as valid predictors of incident CVD and mortality in individuals with hypertension. Graphical abstract